Colombia : Policy Note on the Implementation of Catastrophe Agricultural Insurance - World Bank Group (World Bank, Washington, DC, 2018)
Colombia is very exposed to natural and climatic disasters and especially to large-scale hydro meteorological drought and excess rain or flood events related to the ENSO El Nino or La Nina phenomena which impact very severely on the agricultural sector. In Colombia a high proportion of the rural population are small-scale poor crop and livestock family farmers who are extremely vulnerable to these natural disasters. Since the end of the rural conflict in 2016, Government of Colombia (GoC) has given major priority to the eradication of rural poverty through the regeneration of the agricultural sector with a focus on the most vulnerable small crop and livestock producers located in post conflict municipalities. As part of its commitment to transform the rural sector, GoC is seeking to develop suitable catastrophe agricultural insurance products and programs for the small family farming sector. This Policy Note presents to a series of policy guidelines and recommendations for GoC to consider relating to the design and implementation of large-scale Catastrophe Agricultural Insurance programs as part of the government’s integrated disaster risk management and risk financing strategy for Colombia.